PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES PADA MATA PELAJASAN SOSIOLOGI KELAS X (Tanjungpura University, 2021)
This article describes the development of Google Sites-based learning media and the feasibility of Google Sites learning media from the media and material aspects. The method used is a research and development (RnD) method using the ADDIE development model developed by Dick and Carry. However, in its implementation, only three stages are carried out including Analysis (analysis), Design (design), and Development (development).The results of this study indicate that the development of Google Sites learning media is carried out through three stages, namely the analysis stage, the design stage, and the development stage. The learning media made consist of the Main Page, Competency Page, Material Page, Evaluation Page, Games Page, Announcement Page, and Credit Page. This media was validated by two media experts, two materials experts, and two sociology teachers. The feasibility of Google Sites media is based on the score obtained for each aspect by media experts, material experts, and sociology teachers to get an assessment result with an average score of 4.62 which is included in the appropriate category.